LINGUISTIC STRATEGIES IN THE DISSEMINATION OF HOAXES ON TIKTOK: THE ROLE OF HASHTAGS IN SHAPING PUBLIC MISCONCEPTIONS - Sholihatul Hamidah Daulay; Alya Syahlani Saragih; Lintang Bidadari (Rahis Cendekia Indonesia, 2025)
This study explores how hoaxes spread on TikTok by focusing on the use of language and hashtags as tools to influence public perception. Through the analysis of viral videos from 2025, the research uncovers how strategies like impersonating authority, emotional appeals, and simplified narratives are used to make false information feel convincing. Hashtags such as #fyp, #beritahoax, #deepfake, and #indonesiagelap play an important role in increasing visibility and shaping the tone of the content. These hoaxes often appear relatable, urgent, or credible—even when they are misleading. The findings show that TikTok’s algorithm, combined with the strategic use of language, makes it easy for misinformation to spread and influence how people perceive certain issues. The study highlights how easily misinformation can circulate in emotionally driven digital spaces and why digital literacy is essential to help users recognize and respond to manipulative content.